Tipificar a la temeridad como tipo penal dentro del catálogo de infracción en el código orgánico integral penal - Castro Espinoza, Fausto José (2017)
This research work whose theme is "typify the temerity AS CRIMINAL TYPE WITHIN THE CATALOGUE OF VIOLATION IN THE COMPREHENSIVE ORGANIC PENAL CODE" is oriented or propose a reform of our legal body with the aim of establishing a penalty on the offender a or otherwise cause or causes the victim recklessness. Recklessness is not a virtue but a defect, because although involves courage, this is totally useless, because instead of achieving the objective can put you at risk or increase it. In procedural law recklessness it is go to court petitioning rights absurdities, or answer claims alleging manifestly inconsistent defenses, which goes against judicial economy and in good faith. This must be appreciated strictly speaking, only calling the crazy daredevil those without any legal basis, since otherwise the right of defense at trial would be violated. Furthermore you can set that recklessness is a way to suppress the victim and not recognize rights to it, because in our law is said to be reckless conduct that violates a criminal law when the most basic care is not observed in the implementation of the action, failing to observe rules of prudence that the common people. We are in the field of criminal law punishes acts committed through negligence, the maximum mode or higher degree. It is called recklessness. This thesis Legal Research is structured as follows: First a Conceptual Framework, comprising concepts and definitions, as we have the right to defense, recklessness, as well as other items that will give greater prominence to the proposed theme; doctrinaire framework, covering the doctrines of writers and scholars on the conceptualization of the topic. and a legal framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Organic Code Integral Penal, and then we have a comparative legislation because it helped me to make an analysis of matter from other countries and to extract the most positive. Secondly the research work includes a field study in which surveys and interviews are developed connoisseurs of law in helping me determine or contrast the objectives and hypotheses raised. Third after the analysis of field research we proceeded to the conclusions and recommendations and finally to a legal proposal necessary for the solution of the problem.